Study on the effect of maternal anemia on birth weight of term neonates among rural population India - Gnanasekaran, Sruthy; V., Jakanattane; R., Rajendran R. (International Journal of Contemporary Pediatrics, 2019)
Background: Maternal anemia in pregnancy is common and has several deleterious effects on the health of the mother and the fetus. Maternal anemia is an important risk factor for LBW babies and preterm babies. There exists an insufficient information regarding the adverse effect of anemia during pregnancy especially among rural population. The aim of the study was to determine whether maternal anemia would affect the birth weight of the baby. Methods: The study was conducted in post-natal ward in Sri Venkateshwara Medical College Hospital and Research centre, Ariyur, Puducherry, India a tertiary care hospital in a rural area. Results: About 85% of low birth weight babies were born to mothers with severe maternal anemia with a p value of <0.001 which is statistically significant. None of the mothers who didn't have maternal anemia had low birth weight babies. Conclusions: Maternal anemia is directly proportional to fetal growth. Maternal anemia being an important risk factor for low birth weight should be prevented as early as possible thus helpful in de-creasing the incidence, mortality and morbidity of LBW babies.